Juxtacellular Labeling of Stellate, Disk and Basket Neurons in the Central Nucleus of the Guinea Pig Inferior Colliculus - Wallace, Mark N.; Shackleton, Trevor M.; Thompson, Zoe; Palmer, Alan R. (Frontiers in Neural Circuits, 2021)
We reconstructed the intrinsic axons of 32 neurons in the guinea pig inferior colliculus (IC) following juxtacellular labeling. Biocytin was injected into cells in vivo, after first analyzing physiological response properties. Based on axonal morphology there were two classes of neuron: (1) laminar cells (14/32, 44%) with an intrinsic axon and flattened dendrites confined to a single fibrodendritic lamina and (2) translaminar cells (18/32, 56%) with axons that terminated in two or more laminae in the central nucleus (ICc) or the surrounding cortex. There was also one small, low-frequency cell with bushy-like dendrites that was very sensitive to interaural timing differences. The translaminar cells were subdivided into three groups of cells with: (a) stellate dendrites that crossed at least two laminae (8/32, 25%); (b) flattened dendrites confined to one lamina and that had mainly en passant axonal swellings (7/32, 22%) and (c) short, flattened dendrites and axons with distinctive clusters of large terminal boutons in the ICc (3/32, 9%). These terminal clusters were similar to those of cortical basket cells. The 14 laminar cells all had sustained responses apart from one offset response. Almost half the non-basket type translaminar cells (7/15) had onset responses while the others had sustained responses. The basket cells were the only ones to have short-latency (7–9 ms), chopper responses and this distinctive temporal response should allow them to be studied in more detail in future. This is the first description of basket cells in the auditory brainstem, but more work is required to confirm their neurotransmitter and precise post-synaptic targets.